Bridging Policy and Practice: Local Governance Capacity in Extreme Poverty Alleviation in Jeneponto, Indonesia - Widyawati, Widyawati; Sangkala, Sangkala; Rusdi, Muhammad (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2025)
Extreme poverty challenges sustainable development and demands adaptive, inclusive, and evidence-based governance. This study aims to analyze the institutional capacity of local governments in addressing extreme poverty, focusing on the alignment of national and regional policies, the effectiveness of cross-sectoral coordination, and data governance as a basis for decision-making. The study employed a qualitative method with a case study design in Jeneponto Regency, which has been designated as a priority area for eradicating extreme poverty. Data were obtained through in-depth interviews with 19 key informants, field observations, and official document reviews, and were analyzed thematically using NVivo 12 software. The results indicate a gap in implementation between national policies and regional planning, institutional coordination that is mainly informal and based on personal relationships, and data fragmentation between regional government agencies that hinders the accuracy of program targeting and evaluation. These conditions demonstrate administrative bias and sectoral fragmentation that are as serious as economic bias in hampering the effectiveness of poverty eradication programs. As a conceptual contribution, this study proposes the CARE Framework (Collaboration, Alignment, Responsiveness, Evidence) as an alternative adaptive governance model that places the extreme poor at the center of intervention. This research confirms that successful eradication of extreme poverty requires not only programmatic interventions, but also structural reforms of regional governance that are sustainable, inclusive, and evidence-based.